DETERMINANTS OF FRAUDULENT FINANCIAL STATEMENTS IN INDONESIAN INSURANCE COMPANIES: A FRAUD HEPTAGON APPROACH - Butarbutar, Jesika Kristina; Jannah, Richatul (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
This study investigates the determinants of Fraudulent Financial Statement (FFS) from the perspective of the Fraud Heptagon in insurance companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using purposive sampling, the study obtained 60 firm-year observations from 12 insurance companies based on annual financial statements published by the Indonesia Stock Exchange and the respective company websites. Fraudulent Financial Statement is measured using the Beneish M-Score, while the independent variables represent the seven dimensions of the Fraud Heptagon: pressure (leverage ratio/LEV), opportunity (proportion of independent board of commissioners/BDOUT), rationalization (total accruals to total assets/TATA), capability (change in directors/DCHANGE), arrogance (CEO pictures/CEOPIC), ignorance (corporate governance education/INEDU), and greed (executive director remuneration/EXREMU). The data were analyzed using panel logistic regression with EViews 12. The results indicate that, on a partial basis, only rationalization (TATA) has a positive and significant effect on the likelihood of Fraudulent Financial Statement, whereas the other six variables do not show statistically significant effects. Simultaneously, however, the Fraud Heptagon variables jointly explain the probability of FFS occurrence. These findings suggest that accrual-based rationalization remains the most salient indicator in detecting financial statement fraud in the Indonesian insurance sector, while the explanatory power of the remaining Fraud Heptagon dimensions appears to be context-dependent.